Chapter 5.12 The Profession of Research Management and Administration in Japan - Makiko Takahashi; Shin Ito (Emerald Publishing Limited, 2023)
This chapter outlines the circumstances that led to the evolution of the profession of research management and administration in Japan. The state of research administration in Japan can be characterised by a combination of a top-down approach guided by the government and a bottom-up approach taken by the practitioners named University Research Administrator (URA), which have effectively been working in alignment since 2009. Currently, the RMAN-J (Research Manager and Administrator Network Japan), a national association of URA practitioners and stakeholders, actively promotes networking not only among the practitioners but also with important stakeholders including industries. As a recent achievement, a new skills certification program is being completed based on RMAN-J's activities over the past 13 years.
10.1108/978-1-80382-701-820231046; 10.1108/978-1-80382-701-820231046; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262